Prediction of Stature Based on Foot Length (Journal of Nobel Medical College, 2014)
Background Estimation of body height from its segments or dismember parts has important considerations for identifications of living or dead human body or remains recovered from mass disaster or other similar conditions. Objective Stature is an important consideration in determining the identity. Our aim of the study was to investigate the relationship between foot length and body height and to derive a regression equation for stature estimation from foot length and to find out the correlation between body height and foot length. Methods The present study was conducted on 200 medical students of age group 18 to 23 years studying in MGM Medical College, Navi Mumbai, Maharashtra. India. Body height and foot length were measured in centimeter. All the measurements were taken by using standard measuring devices and standard anthropometric techniques. Results Correlation coefficients between stature and foot dimensions were found to be positive and statistically highly significant. Prediction of stature was found to be most accurate by multiple regression analysis. Conclusions In population similar to our subjects, stature and gender estimation can be done by using foot measurements and it will be helpful for Anatomists, Anthropologists and forensic experts to calculate stature based on foot length. DOI: http://dx.doi.org/10.3126/jonmc.v3i1.10058 Journal of Nobel Medical College Vol.3(1) 2014; 66-70